BINGKAI HETEROSEKSISME DALAM KARYA SASTRA INDONESIA KONTEMPORER BERTEMAKAN HOMOSEKSUALITAS - Yeon, Lee (UI Scholars Hub, 2022)
Since the early 2000’s, Indonesian literary works raising the issue of homosexuality have been increasing in number. However, the proliferation of discourse on homosexuality cannot be necessarily interpreted as Indonesian literature’s increasing sympathy with homosexuality. Adequate discussion is needed regarding perceptions, perspectives, and attitudes towards homosexuality in literary works with the theme of homosexuality. In relation to this, we found that works raising the issue of homosexuality have not been able to escape from the framework of the prevailing social order and norms, namely heterosexism. This study aims to see how the idea of heterosexism works in narrating and embodying homosexuality in six chosen works with the theme of homosexuality. Results show that these six works address the robustness of heterosexism by presenting homosexual characters as individuals who are haunted by confusion about their own sexual orientation, giving stereotypical reasons for being homosexuals, and establishing homosexual relationships with gender roles that operate within the framework of heterosexuality.